Preposition as a grammatical marker of language peculiarities - Nagaitseva, N. I.; Romanov, Yu. (Міжнародний гуманітарний університет, 2016)
The article gives an analysis of the specific lexical and grammatical group of words, prepositions, in terms of teaching Russian as a foreign language; the comparison of Russian and English prepositions is given; the conclusions concerning the methods of teaching Russian prepositions to international students are made.

У статті подано аналіз специфічної лексико-граматичної групи слів – прийменників – із погляду викладання російської мови як іноземної; проводиться порівняння російських і англійських прийменників; зроблено висновки, що стосуються методики викладання російських прийменників іноземним студентам.
Прийменник як граматичний маркер особливостей мови
Keywords: preposition; grammatical marker; meanings of prepositions; monosemy and polysemy; frequency; valence of prepositions; context; structure of prepositions; Russian as a foreign language; прийменник; граматичний маркер; значення прийменників; моносемія; частотність; полісемія; валентність прийменників; контекст; будова прийменників; російська як іноземна; факультет підготовчий